TRANSLATION OF CULTURE-SPECIFIC REFERENCES IN THE TURKISH TRANSLATION OF SHAKESPEARE’S MACBETH - Feride Sümbül (International Journal of Language and Translation Studies)
Drama is a literary genre that mirrors the people and society and transfers the human nature and life to the reader or the audience within its own social-cultural structure. Each play takes on a new reality in the time and culture of the staging, and each performance actually brings a new interpretation to the play. Similarly, each translation adds a new meaning to the source text. In other words, the translated theatrical text transcends the boundaries of its language and culture and finds a new interpretation. Thus, the translation of drama takes place as a transfer from one culture to another as a cross cultural communication. In this context, translating culture specific references play a key role in terms of reflecting cultural aspects of a target society. This study aims to explore the use of Venuti's translation principles of domestication and foreignization in the transfer of culture specific references in the Turkish translation of Shakespeare's Macbeth. Macbeth is compared with its Turkish version in terms of the transference of culture specific references such as religious, cultural, and mythological, which have no equivalent in the target language and culture. To evaluate these principles of Venuti, Davies’s translation strategies are also conducted.